Common dolphins, common in neritic waters off southern Israel, demonstrate uncommon dietary habits. (22nd October 2019) - Brand, Denna; Edelist, Dor; Goffman, Oz; Hadar, Nir; Scheinin, Aviad; Kerem, Dan
Abstract: During the last decade, the common dolphin ( Delphinus delphis ) has become the second most sighted species in Israeli coastal waters, after the common bottlenose dolphin. Documentation mostly relies on opportunistic, photo and/or video‐backed second‐party reports, delimited within a 10 km near‐shore strip. Sightings occur year round, are confined to the southern part of the Israeli coast and typically comprise relatively large groups (mean ± SD: 21.5 ± 13.3), often with young calves. Strandings are relatively scarce, typically one per year, and have so far yielded five upper digestive tract contents for diet analysis. Cephalopods comprised 1.2% of the estimated number of prey items in the combined content. Surprisingly, by far the most abundant and prevalent prey item found (57% of pooled prey items; present and dominant in four out of five tracts) was the Balearic eel ( Ariosoma balearicum ), a sand burrower which is also a major dietary component of the common bottlenose dolphins. Bottlenose dolphins in Israel are known to forage in association with bottom trawlers, leading to the notion that common dolphins also make use of this foraging mode. Indeed, in addition to their association with purse seiners, they have been documented accompanying bottom trawlers, by both day and night. The slender Balearic eels are frequently found protruding from the net's eyes, presumably making easy prey for both dolphin species. Information gaps on common dolphins include range extension to the south/south-west, abundance estimation and genetic flow/isolation. Even so, its unusual diet and the fact that the closest known populations to the north/north-west are from the Aegean Sea, were major considerations in the recent designation of the 'Coastal Shelf Waters of the South-east Levantine Sea' as a Mediterranean Important Marine Mammal Area.